Pengaruh Penambahan Sari Lemon Terhadap Fermentasi Acar (Pickled Cucumber) Timun Berbasis Probiotik - Desi Nurlita (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2025)
The purpose of this study is to illustrate how adding lemon juice affects the fermentation process of cucumber pickles made with probiotics. A mixture of lemon juice, water, and salt was used to carry out the fermentation process. At room temperature, fermentation was carried out for seven days. Changes in pH, solution color, aroma, and the physical state of the cucumbers during fermentation were among the criteria that were noted. According to the findings, the pH progressively dropped from 5.6 on the first day to 4.2 on the seventh, suggesting that lactic acid bacteria activity was creating an acidic environment. The proper fermentation process is indicated by the solution's hue changing to a lighter shade and the emergence of a distinctive sour fermentation fragrance.